Population Pharmacokinetics of Piperaquine in Young Ugandan Children Treated With Dihydroartemisinin‐Piperaquine for Uncomplicated Malaria. Issue 1 (2nd May 2015) - Sambol, NC; Yan, L; Creek, DJ; McCormack, SA; Arinaitwe, E; Bigira, V; Wanzira, H; Kakuru, A; Tappero, JW; Lindegardh, N; Tarning, J; Nosten, F; et al.
<x xml:space="preserve">Abstract</x> This prospective trial investigated the population pharmacokinetics of piperaquine given with dihydroartemisinin to treat uncomplicated malaria in 107 Ugandan children 6 months to 2 years old, an age group previously unstudied. Current weight‐based dosing does not adequately address physiological changes in early childhood. Patients were administered standard 3‐day oral doses and provided 1, 282 capillary plasma concentrations from 218 malaria episodes. Less than 30% of treatments achieved 57 ng/mL on day 7. A three‐compartment model with first‐order absorption described the data well. Age had a statistically significant effect (P < 0.005) on clearance/bioavailability in a model that accounts for allometric scaling. Simulations demonstrated that higher doses in all children, but especially in those with lower weight for age, are required for adequate piperaquine exposure, although safety and tolerance will need to be established. These findings support other evidence that both weight‐ and age‐specific guidelines for piperaquine dosing in children are urgently needed.